Conceptualizations and meanings as ‘cognitive processes’ in the processing of German and Polish phraseologisms - Mazurkiewicz-Sokołowska, Jolanta (Glottodidactica, 2017)
The aim of the paper is an analysis of German and Polish phraseologisms with the focus on processual aspects of their meaning. The central issue of interest is the individual subjective and emotional shaping of conceptualizations and meanings. The conclusions are concerning the mental phenomenon of processual meaning variability, mental spaces and cognitive domains.